Model‐Informed Drug Discovery and Development: Current Industry Good Practice and Regulatory Expectations and Future Perspectives. (1st February 2019) - Marshall, Scott; Madabushi, Rajanikanth; Manolis, Efthymios; Krudys, Kevin; Staab, Alexander; Dykstra, Kevin; Visser, Sandra A.G.
Abstract : Good practices around model‐informed drug discovery and development (MID3) aim to improve the implementation, standardization, and acceptance of these approaches within drug development and regulatory review. A survey targeted to clinical pharmacology and pharmacometric colleagues across industry, the US Food and Drug Administration (FDA), and the European Medicines Agency (EMA) was conducted to understand current and future roles of MID3. The documented standards were generally affirmed as a "good match" to current industry practice and regulatory expectations, with some identified gaps that are discussed. All have seen at least a "modest" step forward in MID3 implementation associated with greater organizational awareness and share the expectation for a future wider use and impact. The priority within organizations was identified as a limitation with respect to the future of MID3. Finally, potential solutions, including a global overarching MID3 regulatory guideline, to facilitate greater acceptance by industry and regulatory decision makers are discussed.